Vocabulary Building Model in Elementary School English Learning - Gede Wira Bayu; Ade Asih Susiari Tantri; I Gusti Ayu Agung Manik Wulandari (Universitas Pendidikan Ganesha, 2025)
Many students still have difficulty understanding English learning due to the lack of supporting learning media and inappropriate learning models. This condition makes the English learning process challenging for students. The aim of this study was to develop a Vocabulary Building Model for English Learning in Elementary Schools. This research used an R&D approach employing the ADDIE model. The research subjects consisted of 2 media experts and 2 material experts, as well as 2 language experts, 2 material experts, and 2 learning experts. The trial subjects included 1 teacher/practitioner, 3 students (individual trial), and 6 students (small group trial). Data were collected using observation, interviews, questionnaires, and tests. The instruments used were questionnaire sheets and test items. Data analysis techniques applied in this study included qualitative descriptive analysis, quantitative descriptive analysis, and inferential statistics. The results showed that language experts gave a validity score of 95% (very valid), material experts 92% (very valid), and learning experts 90% (very valid). The individual trial obtained a practicality score of 95% (very practical), the small group trial scored 96% (very practical), and the teacher assessment was 90% (very practical). The effectiveness test results indicated an improvement in student learning outcomes after implementing the Vocabulary Building Model in Elementary School English Learning. It can be concluded that the Vocabulary Building Model is feasible for use in English learning and can enhance English learning outcomes for elementary school students.